1969
DOI: 10.1017/s0021859600020116
|View full text |Cite
|
Sign up to set email alerts
|

The artificial rearing of calves and their growth on grass diets: II. The effect of length of period of feeding cold milk substitute to spring–born calves at pasture

Abstract: An experiment was conducted with 32 spring-born Friesian heifer calves, purchased at an average age of 10 days and fed on cold reconstituted milk substitute at pasture.The milk feeding treatments were 4, 4£, 6J and 9J weeks in length, during which time calves consumed an average of 17, 23, 43 and 70 kg dry matter/head of milk substitute respectively. The differences between treatment mean live-weight gains for 10£ weeks of the experiment were highly significant (P < O'OOl): the gains were 0-49, 0-43, 0-64 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1970
1970
1991
1991

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…1959;Everitt 1972a;Reardon & Everitt 1972) illustrate that the early postnatal period in cattle is particularly sensitive to under-feeding, with long-term effects. Other studies with single-born calves confirm this view and show that the stunting effect is not due solely to a small pre-natal penalty suffered by twins (Burt & Bell 1962;Wardrop 1966;Everitt et al 1969;Lonsdale & Tayler 1969;M.L.C. 1971a;Gleeson 1971;Everitt 1972b;Byford 1973;Smith et al 1973;Dalton et al 1975;Kaiser & O'Neil 1975;Everitt et at.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…1959;Everitt 1972a;Reardon & Everitt 1972) illustrate that the early postnatal period in cattle is particularly sensitive to under-feeding, with long-term effects. Other studies with single-born calves confirm this view and show that the stunting effect is not due solely to a small pre-natal penalty suffered by twins (Burt & Bell 1962;Wardrop 1966;Everitt et al 1969;Lonsdale & Tayler 1969;M.L.C. 1971a;Gleeson 1971;Everitt 1972b;Byford 1973;Smith et al 1973;Dalton et al 1975;Kaiser & O'Neil 1975;Everitt et at.…”
Section: Discussionmentioning
confidence: 92%
“…Ioblin (1968) showed that the degree of compensation achieved in cattle was positively related to the level of feeding in the re-alimentation period. Compensatory growth during the recovery period in young calves is less likely on bulky feeds such as pasture (Lonsdale & Tayler 1969;Byford 1973) than on highly digestible, low bulk concentrate feeds (Aitken et al 1963;Swart & Swart 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Fine-milled dried grass or lucerne age do not, however, display marked compensatory growth on grass diets (14). It is necessary, therefore, to know whenever possible (a) the empty-weight or carcass-weight gains and (b) the weight-for-age of cattle in relation to existing or proposed standards for growth rate.…”
Section: Exptmentioning
confidence: 99%
“…For the animals which grazed at the higher intensity this relationship was significant (P<0 05). Other workers have noted that restriction in rate of gain prior to 3 months of age is not associated with subsequent compensating growth (16,17,22).…”
Section: Discussionmentioning
confidence: 95%